MTOR–RAPTOR and 14-3-3σ immunohistochemical expression in high grade prostatic intraepithelial neoplasia and prostatic adenocarcinomas: a tissue microarray study. Issue 8 (8th June 2011) - Evren, Sevan; Dermen, Arthur; Lockwood, Gina; Fleshner, Neil; Sweet, Joan
Abstract : Background: The mammalian target of rapamycin (mTOR) is a serine/threonine protein kinase which associates with regulatory-associated protein of TOR (RAPTOR), forming the mTORC1 complex, which is necessary for activation of the mTOR pathway. 14-3-3σ belongs to a family of proteins known to regulate the mTOR–RAPTOR interaction and signalling of this cascade. The mTOR pathway is a key regulator of protein synthesis and growth and is up-regulated in many cancers. The correlation of mTOR, RAPTOR and 14-3-3σ in high grade prostatic intraepithelial neoplasia (HGPIN) and prostate cancer has not previously been investigated. Aims: To examine the immunohistochemical expression of phosphorylated mTOR (p-mTOR), RAPTOR and 14-3-3σ in HGPIN and prostatic adenocarcinoma (PCa) using tissue microarrays. Methods and results: There were contrasting immunohistochemical patterns of expression for mTOR and 14-3-3σ in HGPIN and PCa. Cochran–Armitage analysis demonstrated decreasing p-mTOR and increasing 14-3-3σ expression, progressing from PIN through GL6 and GL7 to high grade PCa. In cores with coexistent staining for 14-3-3σ and p-mTOR, the expression of each marker was restricted to different geographical areas of an individual core. Conclusion: The inverse correlation of p-mTOR and 14-3-3σ expression supports the role of 14-3-3σ as an inhibitor of p-mTOR activity in the prostate. The extent of 14-3-3σ and mTOR expression in an individual patient with prostate cancer would determine how effective the use of mTOR inhibitors would be as potential therapeutic agents.